1999
DOI: 10.1889/1.1834070
|View full text |Cite
|
Sign up to set email alerts
|

LP‐3: Late‐News Poster: Photoalignment Materials Based on ω‐(4 ‐Chalconyloxy) Alkyl Groups Providing TN Alignment with Pretilt Angle by One‐Step Exposure of Polarized Near‐UV Light

Abstract: New photo LC alignment materials based on poly (ω ‐(4‐chalconyloxy) alkoxyphenyl maleimide) were synthesized and evaluated. On the films of these materials, LC alignment was regulated parallel to the polarization plane of the exposed LPUV at a large dose, and thus generated pretilt angle among 1–5° by one‐step slantwise LPUV exposure. TN cells were fabricated using these materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…[13][14][15][16][17][18][19] Makita et al reported that the good LC alignment was observed for the LC cell using the polymer film with a chalcone moiety compared to the cinnamate polymer film when the deep UV light was cut off. [13][14][15][16] So the chalconyl moiety is a good photosensitive group. Poly(4-methacryloyloxy chalcone) (PM4Ch) or poly(4 -methacryloyloxy chalcone) (PMCh) were employed as a photoalignment film.…”
mentioning
confidence: 99%
“…[13][14][15][16][17][18][19] Makita et al reported that the good LC alignment was observed for the LC cell using the polymer film with a chalcone moiety compared to the cinnamate polymer film when the deep UV light was cut off. [13][14][15][16] So the chalconyl moiety is a good photosensitive group. Poly(4-methacryloyloxy chalcone) (PM4Ch) or poly(4 -methacryloyloxy chalcone) (PMCh) were employed as a photoalignment film.…”
mentioning
confidence: 99%
“…[13][14][15][16][17][18][19]22,26,27,32 The alignment direction of 5CB in the LC cell using the irradiated poly(4-methacryloyloxy chalcone) (PM4Ch) film was perpendicular to the electric vector of the incident LPUV light.…”
Section: Alignment Of 5cb In Lc Cell Fabricated From Irradiated Polyimentioning
confidence: 99%
“…Non-mesogenic photosensitive polymers containing chalcone derivatives have been studied for the photo-alignment film. [13][14][15][16][17][18][19] The alignment of LC molecules is easily improved by the surface of LC polymers that exhibit a mesophase. This idea arises from the simple role of solubility for organic compounds, that is, like dissolves like.…”
mentioning
confidence: 99%
“…Photosensitive polymers containing chalcone derivatives have been studied for the photo-alignment film. [14][15][16][17][18][19][20] The alignment behavior of the LC molecules would be easily improved by the liquid crystalline polymer surface where mesogenic groups having similar chemical structure to that of the LC molecules existed. This idea would arise from similar behavior to the solubility of the organic compounds, that is to say, like dissolves like.…”
Section: Introductionmentioning
confidence: 99%